Longevity Rituals in the Bon Phur pa tradition: Chapter 25 of the Black Pillar - Cantwell, C; Mayer, R (Vajra Books, 2015)
In the pages below we present a translation of the chapter on longevity from a famous canonical Bon tantra, considered to be the root text for the entire and highly influential Bon Phur pa tradition. The text in question is the Black Pillar Secret Pith instruction root Tantra (ka ba nag po man ngag rtsa ba’i rgyud) in 39 chapters, the first and most important of the cycle of nine Phur pa tantras revealed by Khu tsha zla ’od at sPa gro cal gyi brag or Phug cal in Bhutan, some time in the eleventh or twelfth century.